Strategi Pembangunan dalam Upaya Meningkatkan Perekonomian di Desa Jatimulyo Kecamatan Jenggawah Kabupaten Jember - Mahsun Mahsun (Indonesian Journal of Research and Service Studies, 2024)
Mahsun. 2161201504. Development Strategy to Improve the Economy in Jatimulyo Village, Jenggawah District, Jember Regency. Management Study Program, Ahmad Dahlan Institute of Technology and Business, Jakarta. Supervisor: HUSNAYETTI, SE., M.M. The Jatimulyo Village Government, Jenggawah District, Jember Regency, is the driving force behind implementing the National Development program in the village. The purpose of this study is to determine the development strategy in Jatimulyo Village, Jenggawah District, Jember Regency, from planning, implementation, and supervision, and to determine how the Jatimulyo Village Government improves the economy. This research is a qualitative descriptive study. The data sources used are primary and secondary data. The data collection techniques used were observation, interviews, and documentation. Data analysis was carried out through the process of data collection, data reduction, data presentation, and drawing conclusions. Development Strategy in Efforts to Improve the Economy in Jatimulyo Village, Jenggawah District, Jember Regency has been implemented well starting from the planning stage, implementation of development and supervision can be said to be in accordance with the applicable regulations and laws, however, even though the implementation of the development has had a direct impact on the village community, in reality it has not been fully able to improve the economy of the Jatimulyo Village community and has not been able to eradicate poverty in the Village.